Agha Shahid Ali and the Phenomenology of Postcolonial Nostalgia. Issue 7 (2nd October 2020) - Nelson, Matthew
Abstract : Scholars have generally analyzed nostalgia in cognitive terms – the ideas of home it traffics in, the stories it tells itself about the world, the narratives its subjects imagine themselves acting in. Through readings of two poems by Kashmiri-American Agha Shahid Ali, this essay argues against such cognitive focus, proposing instead an affect-minded account of nostalgia that draws on phenomenological research so far ignored in both literary and postcolonial scholarship. In particular, it argues the homes desired by nostalgia are inherently ambiguous and underdetermined. Realizing this forces us to abandon common typologies of nostalgia that rely on the assumption of a clear object of desire, such as Svetlana Boym's influential distinction between "reflective" and "restorative" types. Instead, the essay argues we must attend to nostalgia as the affective negotiation of an interruption of the present by a sense of familiarity lost, familiarity moreover that one knows of (at that moment) only through a gestalt of a past era or season.